Thyrotoxic Periodic Paralysis and its Management: A Case Report - Nimat Alam; Linda Esteban; Enrique Tobias; Jenet George (Medical Science: Recent Advances and Applications Vol. 1, 2025)
Thyrotoxic periodic paralysis (TPP) is characterized by the abrupt onset of hypokalemia and paralysis. This condition primarily affects the lower extremities but may affect both upper and lower extremities and is secondary to thyrotoxicosis. It is most commonly seen in Asian men, and it has been increasingly reported in the USA due to the rise in the immigrant population. Hypokalemia in TPP results from an intracellular shift of potassium induced by the thyroid hormone sensitization of Na+/ K+ ATPase rather than depletion of total body potassium. In this case report, A 31-year-old Hispanic male arrived at the Emergency Room by Emergency Medical Service with complaints of lower and upper Extremities weakness. The patient was diagnosed with TPP due to the patient’s past medical history and latest symptoms. There are other differential diagnoses that could present with extremity paralysis, such as Guillain-Barré syndrome, meningitis, Stroke, medication side effects, or even malignancy. But TPP is one of the diagnoses often missed due to its low occurrence and also because of unawareness about this disorder. Therefore, increased awareness among physicians regarding this condition would also result in early diagnosis, appropriate management, and prevention of thyrotoxic periodic paralysis.